Alcohol and Drug Use, Pain and Psychiatric Symptoms among Adults Seeking Outpatient Psychiatric Treatment: Latent Class Patterns and Relationship to Health Status. Issue 1 (1st January 2018) - Ramo, Danielle E.; Bahorik, Amber L.; Delucchi, Kevin L.; Campbell, Cynthia I.; Satre, Derek D.
ABSTRACT: Background : Substance use, psychiatric problems, and pain frequently co-occur, yet clinical profiles of treatment-seeking patients are poorly understood. To inform service and treatment planning, substance use and symptom patterns were examined in an outpatient psychiatry clinic, along with the relationship of these patterns to demographic characteristics and physical health. Methods : Patients ( N  = 405; age M  = 38; 69% White; 60% female) presenting for intake in a psychiatry outpatient clinic completed a computerized assessment of psychiatric problems, drinking, and drug use. Substance use and psychiatric symptom patterns among the sample were identified using latent class analysis. Results : A 4-class model fit the data best: Class (1) Moderate symptoms/wide-range users (22.0%) had moderate depression and panic; tobacco, cocaine, hallucinogen, and ecstasy use; and high cannabis use. Class (2) Moderate depression/panic (37.8%) had moderate depression and panic. Class (3) Depression/anxiety, tobacco, and cannabis users (28.0%) had high depression, obsessions, and panic, and moderate pain severity, social phobia, compulsions, trauma, tobacco, and cannabis use. Class (4) Severe/wide range symptoms/users (12.0%) had high panic, depression, social phobia, obsessions, drug use, and moderate pain. Gender, ethnicity, and health status varied by class. Conclusions : Findings highlight the preponderance of substance use (particularly cannabis) and its relationship to psychiatric symptom severity, pain, and health status among those presenting for mental health treatment.